Effect of amelioration on growth and yield of two groundnut varieties on saline soil - A Taufiq; A Wijanarko; A Kristiono (Brawijaya University, 2016)
Productivity of agricultural land in coastal area is limited by salinity. Planting tolerant variety combined with amelioration is an effective management to increase productivity of salt affected land. The objective of this study was to identify effective ameliorant for improving growth and yield of groundnut on saline soil. The trial was conducted on saline soil in Tuban from May to September 2015. The trial consisted of two factors that were arranged in a completely randomized block design, three replications. The first factor was two groundnut varieties (Domba and Hypoma 1). The second factor was six soil ameliorations (control, 120 kg/ha K2O, 2.5 t/ha dolomite, 2,5 t/ha of gypsum, 2.5 t/ha of manure, and 1.5 t/ha of gypsum + 2.5 t/ha of manure). Results showed that Domba and Hypoma 1 varieties could tolerate and completed their life cycle at insitu saline condition. Hypoma 1 was more prospective to be developed in saline condition associated with higher survival as well as better pod setting and seed development than Domba. Combination of gypsum and manure provided better effect than other treatments in improving saline soil, since it reduced exchangeable Na, Na saturation, and EC of soil, and also improved groundnut yield.